Dynamic linkages between transport, logistics, foreign direct Investment, and economic growth: Empirical evidence from developing countries. (November 2020) - Saidi, Samir; Mani, Venkatesh; Mefteh, Haifa; Shahbaz, Muhammad; Akhtar, Pervaiz
Highlights: We study the dynamic linkages among transport, logistics, FDI and economic growth. Empirical investigation considers 46 developing countries between 2000 and 2016. The 46 countries have been divided into three sub-groups. We use the GMM estimators for econometric investigation. Positive and significant causal relationships are found between the variables. Abstract: This study examines the relationship between transport, logistics, foreign direct investment (FDI), and economic growth in developing countries over the period 2000–2016. A global panel data comprising of 46 developing countries were collected and divided into three sub-panels: European and Central Asian countries (ECA), Middle East, North African and Sub-Saharan countries (MENA-SSA), and East Asian, Pacific, and South Asian countries (EAPSA). Using GMM estimators, we found that all underlying variables influence each other in the long-run. The direction of causal relationship between the variables tended to vary across panels with different levels of significance. The results arising out of empirical analysis imply that transport and logistics infrastructure do contribute to FDI 'attractiveness' and sustainable economic growth. These results would be of particular interest to policymakers, working in developing countries, and help them design and develop modern transportation and logistics, coupled with interlinked technological factors, which could possibly be used for sustainable economic development, and which in turn would attract FDI.